SOCIAL LITERATURE AND CENSORSHIP IN THE USA AT THE BEGINNING OF THE 20TH CENTURY - Aleksander Sivilov (Издател, 2025)
The text examines the manifestations of censorship on socially engaged literature in the USA during the first half of the 20th century, focusing on three emblematic works: Upton Sinclair’s The Jungle, Theodore Dreiser’s An American Tragedy, and John Steinbeck’s The Grapes of Wrath. The author considers censorship not only as the restriction of information but also as a means of political and moral control within so-called democratic societies. Each of the three works provoked sharp public and institutional reactions due to its social critique, leading to bans, surveillance by agencies, and pressure on the authors. Specific censorship mechanisms are indicated – from laws like the Comstock Acts to self-censorship by publishers and editors. The text defends the thesis that social literature in the USA played a crucial role in exposing societal contradictions, despite efforts to suppress it.